2021
DOI: 10.1002/pbc.29138
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric myelodysplastic syndrome with inflammatory manifestations: Diagnosis, genetics, treatment, and outcome

Abstract: Background Inflammatory manifestations (IM) are well described in adult patients with myelodysplastic syndrome (MDS), but the presentation is highly variable and no standardized treatment exists. This phenomenon is rarely reported in children. As more pediatric patients are hematopoietic stem cell transplantation (HSCT) candidates, the role of anti‐inflammatory treatment in relation to HSCT should be defined. Procedure Here, we report a series of five children from a tertiary center. We describe the clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…At the same time, anti‐inflammatory treatment might serve as a bridge to allow JMML patients with BD undergo allo‐HSCT in better clinical condition. Systemic corticosteroids are considered the basis of treatment; however, a significant proportion of patients may require dual‐ or even third‐line therapy, such as immunomodulating agents and monoclonal antibodies 18 . Moreover, it has been reported that repeated cycles of hypomethylating agents can impact BD, resulting in a significant reduction in steroid dosage and dependency among a substantial number of patients 4,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, anti‐inflammatory treatment might serve as a bridge to allow JMML patients with BD undergo allo‐HSCT in better clinical condition. Systemic corticosteroids are considered the basis of treatment; however, a significant proportion of patients may require dual‐ or even third‐line therapy, such as immunomodulating agents and monoclonal antibodies 18 . Moreover, it has been reported that repeated cycles of hypomethylating agents can impact BD, resulting in a significant reduction in steroid dosage and dependency among a substantial number of patients 4,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Systemic corticosteroids are considered the basis of treatment; however, a significant proportion of patients may require dual-or even third-line therapy, such as immunomodulating agents and monoclonal antibodies. 18 Moreover, it has been reported that repeated cycles of hypomethylating agents can impact BD, resulting in a significant reduction in steroid dosage and dependency among a substantial number of patients. 4,19 Furthermore, pre-transplantation azacitidine therapy has been reported as a suitable strategy to facilitate allo-HSCT and the outcomes are deemed satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients with constitutional trisomy 8 [ 22 , 38 , 39 ] and patients with trisomy 8 in their bone marrow [ 19 21 , 23 , 40 , 41 ] have been reported to exhibit Behcet’s disease (BD) or other inflammatory disorders. CRP and interleukin (IL)-6 levels were significantly increased in patients with trisomy 8 during acute inflammation [ 20 , 42 ]. Inflammatory manifestations related to trisomy 8 in children are rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients in our study diagnosed with trisomy 8 had symptoms similar to BD, along with increased CRP/ESR levels and elevated IL-6 levels. Treatment with anti-inflammatory medications, such as systemic steroids, can improve clinical symptoms [ 20 , 39 ]. Trisomy 8 is also thought to increase the risk of the development of malignancy, especially myelodysplastic syndrome (MDS) symptoms [ 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation